2022
DOI: 10.3390/foods11213328
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stabilized Rice Bran Addition on Physicochemical, Sensory, and Techno-Functional Properties of Bread

Abstract: Rice bran (RB) is a valuable byproduct derived from rice milling that represents an excellent opportunity for dietary inclusion. Bioactive components with antioxidant potential have been reported in RB, gaining the considerable attention of researchers. However, RB requires a stabilization process after milling to prevent it from becoming rancid and promote its commercial consumption. The aim of this study was to evaluate the effects of substituting stabilized rice bran (SRB) for wheat flour at levels of 10, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Three rice bran samples, FFRB, CPRB, and DFRB, were analyzed using the method described by Espinales et al [ 28 ], with slight modifications. Fifty (50) grams of the sample was placed in a stainless steel can, steam-heated at 121 °C for 20 min, allowed to air-dry overnight, then dried in a hot-air oven at 60 °C for 24 h. The obtained powder samples, namely sFFRB, sCPRB, and sDFRB, were passed through sieve no.…”
Section: Methodsmentioning
confidence: 99%
“…Three rice bran samples, FFRB, CPRB, and DFRB, were analyzed using the method described by Espinales et al [ 28 ], with slight modifications. Fifty (50) grams of the sample was placed in a stainless steel can, steam-heated at 121 °C for 20 min, allowed to air-dry overnight, then dried in a hot-air oven at 60 °C for 24 h. The obtained powder samples, namely sFFRB, sCPRB, and sDFRB, were passed through sieve no.…”
Section: Methodsmentioning
confidence: 99%
“…The use of pre-treatment is an option to manage phytic acid content. Stabilizing rice bran decreased the phytic acid content and prevented the rice from going rancid, and the germination of rice also decreased the phytic acid content [16,17].…”
Section: Research Recommendations/futurementioning
confidence: 99%
“…An important source of edible oil is rice bran, which can represent up to 20% of the oil's weight [66]. A recent study indicated that substituting stabilized rice bran (after grinding, a stabilization process is required to prevent rancidity) for wheat flour resulted in a significant increase in total antioxidant activity, total dietary fiber content, ashes, and bioactive compounds; however, the results indicated that up to 15% replacement of wheat flour affects the overall physical properties of the dough and the sensory attributes of the bread [67]. Stabilized rice bran improves nutritional value and texture characteristics, thereby promoting the consumption of bakery and pastry products that contribute to a healthy diet, such as biscuits [68,69] and muffins [70].…”
Section: Conventional Milling the Major Supplier Of Grain Losses Reus...mentioning
confidence: 99%